Core-Substituted Naphthalene-Diimides (cNDI) and Related Derivatives: Versatile Scaffold for Supramolecular Assembly and Functional Materials - Mukherjee, Anurag; Ghosh, Suhrit (Organic Materials, 2021)
Naphthalene-diimide (NDI)-derived building blocks have been explored extensively for supramolecular assembly as they exhibit attractive photophysical properties, suitable for applications in organic optoelectronics. Core-substituted derivatives of the NDI chromophore (cNDI) differ significantly from the parent NDI dye in terms of optical and redox properties. Adequate molecular engineering opportunities and substitution-dependent tunable optoelectronic properties make cNDI derivatives highly promising candidates for supramolecular assembly and functional materials. This short review discusses recent development in the area of functional supramolecular assemblies based on cNDIs and related molecules.Table of contents1. Introduction2. General Supramolecular Assemblies of cNDI Derivatives3. cNDI-Based Chiral Supramolecular Assemblies and Functional Materials4. Controlled Supramolecular Polymerization with cNDI Derivatives5. Dimeric Naphthalimide-Based Building Blocks6. Conclusions and Outlook
Keywords: π-conjugated chromophores; naphthalene-diimides; core substitution; supramolecular polymerization; chiral recognition; functional materials